Corrosion protection of N80 steel in hydrochloric acid medium using mixed C15H15NO and Na2WO4 inhibitors - Hu, Jun (2019)
A novel inhibitor based on mixed Mannich base (C15H15NO) and Na2WO4 was developed for the corrosion prevention of N80 steel in hydrochloric acid solution. Infra-red spectrum, electrochemical measurements, X-ray Photoelectron Spectroscopy, and Scanning Electron Microscopy were used to understand the inhibition efficiency and mechanism. The results showed that the mixed inhibitors reduced the corrosion current density and increased the interface resistance. The inhibition efficiency is the highest when the ratio of C15H15NO to Na2WO4 is 1:1 in the mixture. Observed from the surfaces, the number of pits and small cracks was reduced on the surface in the presence of the optimized inhibitors. The inhibition film can successfully hinder the chloride ions from reaching the bulk steel.